A Cure for HIV Infection: "Not in My Lifetime" or "Just Around the Corner"? - Michael M. Lederman; Paula M. Cannon; Judith S. Currier; Carl H. June; Hans-Peter Kiem; Daniel R. Kuritzkes; Sharon R. Lewin; David M. Margolis; Joseph M. McCune; John W. Mellors; Timothy W. Schacker; Rafick P. Sekaly; et al. (Case Western Reserve University, 2016)
With the advent and stunning success of combination antiretroviral therapy (ART) to prolong and improve quality of life for persons with HIV infection, HIV research has been afforded the opportunity to pivot towards studies aimed at finding "a cure." The mere idea that cure of HIV might be possible has energized researchers and the community towards achieving this goal. Funding agencies, both governmental and private, have targeted HIV cure as a high priority; many in the field have responded to these initiatives and the cure research agenda is robust. In this "salon" two editors of Pathogens and Immunity, Michael Lederman and Daniel Douek ask whether curing HIV is a realistic, scalable objective. We start with an overview perspective and have asked a number of prominent HIV researchers to add to the discussion.